2018
DOI: 10.2298/fuee1802207r
|View full text |Cite
|
Sign up to set email alerts
|

Construction of subsets of bent functions satisfying restrictions in the Reed-Muller domain

Abstract: Our society greatly depends on services and applications provided by mobile communication networks. As billions of people and devices become connected, it becomes increasingly important to guarantee security of interactions of all players. In this talk we address several aspects of this important, many-folded problem. First, we show how to design cryptographic primitives which can assure integrity and confidentiality of transmitted messages while satisfying resource constrains of low-end low-cost wireless devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It was shown that using restrictions of binary functions in the Reed-Muller (RM) domain, the set of functions can be split into the spectral subset with respect to three different criteria related to the properties of RM-spectra of bent functions. The vertical, horizontal, and grid RM subsets are defined [8]. Experimental results showed some interesting properties of different subsets in the spectral RM domain which can be helpful in designing construction methods for obtaining bent functions.…”
Section: Copyright Cmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that using restrictions of binary functions in the Reed-Muller (RM) domain, the set of functions can be split into the spectral subset with respect to three different criteria related to the properties of RM-spectra of bent functions. The vertical, horizontal, and grid RM subsets are defined [8]. Experimental results showed some interesting properties of different subsets in the spectral RM domain which can be helpful in designing construction methods for obtaining bent functions.…”
Section: Copyright Cmentioning
confidence: 99%
“…Since the algebraic degree of n-variable p-valued bent functions in the polynomial form is at most ⌈n/2⌉ for n > 2, the possible positions of the non-zero coefficients in the spectrum of bent functions are restricted. By using the same feature in the case of binary bent functions, we proposed in [8] splitting the set of all Boolean bent functions with respect to three different criteria related to the properties of their RM spectra. In this paper, the approach is generalized to ternary and quaternary functions.…”
Section: Subsets Of Bent Functions In Gf and Rmf Domainsmentioning
confidence: 99%
See 1 more Smart Citation